Evaluación de la seguridad y salud ocupacional en el departamento de obras públicas del Gobierno Autónomo Descentralizado del cantón Tosagua - Cedeño Cedeño, Betty Gabriela (2021)
This study was developed under the theme of Occupational Safety and Health (OHS), being the management related to the quality of life, environment and health of human resources in an occupation. This work sought to evaluate the (SSO) of the public works department of the Autonomous Decentralized Government (GAD) in Tosagua canton for the development of an improvement plan that contributes to the prevention of accidents and occupational diseases. Initially, two information collection instruments were used, which include the structured interview applied to the manager in charge of managing the (OHS) in the institution, on the other hand, the application of the survey to the workers of the intervened department was required, with a questionnaire distributed by the study variables, dimensions and questions with Likert-type evaluative scales, likewise, the use of an improvement plan was used to determine and establish corrective actions to inconsistencies found. The results obtained from the used methodology showed disappointment about what was said by the manager compared to the results of the questionnaire instrument, since inconsistencies were reflected such as lack of training, little implementation of protective equipment, signaling of work areas, equipment of supplies and knowledge in first aid, psychological evaluations and lack of hygiene in the use of facilities and handling of harmful substances. Finally, these factors could have repercussions on the physical and mental health of workers if the improvement of the problems encountered is not considered.